Growth Performance of Lettuce Using Fermented Products as Organic Fertilizers - Kareen Lynn E. Negado (Alliance of Health Activists (AloHA), 2019)
This study evaluates the growth performance of lettuce (Lactuca sativa L.) utilizing various fermented products as organic fertilizers. Growth performance is determined through the plant’s weight and leaves and significant differences in growth among various treatments: (a) fish trash, (b) scrap seaweeds, (c) kangkong, and control groups urea (positive) and water (negative) was also determined. Kangkong leaves are fermented for 10 days, fish trash for 14 days and 1 month for seaweeds. Lettuce seeds are sown before transplanting (15 days after germination) into pots and placed in raised beds. Randomized complete block design is utilized in the experiment. Growth performance is measured through the number of leaves 10, 20, and 30 days after transplant and mass of plant upon harvest. After 30 days, the lettuce was harvested. Based on the findings, the soil and fermented products are acidic and the needed organic matter for optimum growth of lettuce are not sufficient as well as some nutrients of the fermented products. Among the organic fertilizers, kangkong at 30 ml performs best in terms of the growth performance of lettuce. Urea performs best in terms of the mass upon harvest. Significant differences exist in the mean number of leaves of lettuce treated with various amounts of organic fertilizers with the plants that receive urea. Lettuce produce more number of leaves and with the highest mass upon harvest when treated with urea compared with organic fertilizers applied after 30 days from transplant. Keywords: fermented kangkong; fish trash; growth performance; lettuce; scrap seaweeds